Combined effect of fructose and NaCl on the viscosity of alumina nanopowder suspensions. Issue 1 (January 2015) - Çınar, Simge; Anderson, Daniel D.; Akinc, Mufit
Abstract: Many ceramic processing operations involving powder suspensions aim to optimize the solids loading while maintaining low viscosity. Use of nanopowder suspensions are challenging as they exhibit unexpectedly high viscosities. Low molecular weight saccharides were added to decrease the viscosities of alumina nanopowder suspensions as they modify effective solids content. It was also recently reported that suspensions with very low ionic strengths exhibit lower viscosities as they create high repulsive barrier between the particles. In the present study, the effect of the combination of these two additives on the viscosity is reported. Low temperature differential scanning calorimetry (LT-DSC) and in situ attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR) results showed that two additives act independently. Suspensions containing NaCl and fructose yield green compacts with lower porosity and higher strength.